On the seasonality of droughts in the lowlands of Sarawak (Borneo) - Bruning, Eberhard F. (ERDKUNDE, 1969)
The long-term averages of monthly precipitation, temperature and humidity characterize the climate of the Sarawak lowlands as an ever-humid equatorial rainforest climate. A comparison of sliding 30-day totals of precipitation from July 1963 to July 1965 at five observation stations with the distribution of precipitation levels in the corresponding months at three observation stations shows that droughts also occur regularly in this climate type. For forest vegetation, this means not only a reduction in net organic matter production, but also a promotion of morphological and phenological traits adapted to these dry conditions. The doubts about the actual existence of an always humid equatorial rainforest climate in the tropical lowlands are confirmed for Sarawak.